Daur at-Tarbiyyah al-Islamiyyah fi Nasyr ats-Tsaqafah al-Qanuniyyah fi al-Mujtama‘ al-Muslim - Mohammad Umar Hafiz Mohammad Idrees; Mohammad Taufiq (el Harakah: Jurnal Budaya Islam, 2022)
تميزت التربية الإسلامية بسمات وخصائص أضفت على منهجها الشمولية المتكاملة فيما يحتاجه الإنسان في معاشه ومعاده وعلاقاته المختلفة، بما يتوافق مع الفطرة الإنسانية، فهي تربية ربانية متوازنة، لا يطغى فيها الجانب الروحي على الجانب الجسدي أو العكس، كما تتسم بالثبات في قواعدها ومبادئها الكلية، والمرونة في جزئياتها وتفصيلاتها المستجدة، والواقعية المتوافقة مع القدرات البشرية بعيدًا عن التصورات العقلية المجردة، في توجيه الإنسان للسلوك الواقعي الصحيح القابل للتطبيق العملي، المتمثل في تطبيق القوانين العامة للمجتمع المسلم، المنبثقة من مبادئ التشريع الإسلامي Islamic education was characterized by features and characteristics that added to its method the integrated comprehensiveness of what people need in their livelihood, their hereafter, and their various relationships in accordance with human innateness. It is a balanced divine education, in which the spiritual side does not dominate over the physical side, or vice versa. It is also characterized by stability in its rules, universal principles, flexibility in its parts, Up-to-date details, and realism, which are compatible with human capabilities away from abstract mental perceptions. Furthermore, it is characterized by human guidance for the correct realistic behavior that is practicable. This behavior is represented in the application of the general laws of the Muslim society that emanate from the principles of Islamic legislation.